Similar Dependence of Acuity Measures on Exposure Duration Irrespective of Acuity Level in Artificially Degraded Vision. (3rd April 2021) - Heinrich, Sven P.
ABSTRACT: Purpose: The duration of optotype presentation in a visual acuity test is an important co-determinant of the test outcome. Most typically, acuity tests are self-paced, which implies an influence of personality on visual acuity test results and a possible lack of transferability to dynamic real-world conditions. Previous studies demonstrated a strong detrimental effect on acuity in the sub-second range, while also revealing further improvement for longer presentation durations of multiple seconds. These studies were performed with normal vision and proposed, besides signal integration, small physiological fluctuations in retinal image quality as underlying the duration effect. In the present study, these fluctuations are overridden by artificial degradation of vision in order to assess their relevance. Methods: Visual acuity was measured with the Freiburg Acuity and Contrast Test with 5 different optotype presentation durations (0.1–10 s). Each of 16 participants was tested with normal vision and with artificially degraded acuity. Results: The overall dependence of acuity on presentation duration was similar for normal and degraded vision ( r 2 = 0.9). In both conditions, the largest detrimental effect was in the sub-second range at 0.1 s. A statistically significant, albeit small, improvement with longer viewing time was only present with degraded vision. Conclusions: The present study confirms previous findings also for the case of reduced acuity. The data suggest that small physiological fluctuations in retinal image quality are not a dominant factor regarding the effect of presentation duration. Overall, and in particular for sub-second presentation durations, there is little difference between normal and degraded vision.